Dual-gate organic phototransistor with high-gain and linear photoresponse - Philip C. Y. Chow (Nature Portfolio, 2018)
High-resolution imaging technologies call for photodetectors with high-gain and linear response over a large dynamic range. Chow et al. show a dual-gate structure that combines the operation of photodiodes and phototransistors to enable both amplified and linear response without external circuitry.